FOOTBALL RESEARCH IN BRAZIL: ANALYSIS OF SCIENTIFIC RESEARCH GROUPS AND RECENT SCIENTIFIC PRODUCTION A PESQUISA SOBRE O FUTEBOL NO BRASIL: ANÁLISE DOS GRUPOS DE PESQUISA E DA PRODUÇÃO CIENTÍFICA RECENTE LA INVESTIGACIÓN SOBRE EL FÚTBOL EN BRASIL: ANÁLISIS DE LOS GRUPOS DE INVESTIGACIÓN Y DE LA PRODUCCIÓN CIENTÍFICA RECIENTE - da Cruz W.M.* (2022)
© 2022, Universidade Federal do Rio Grande do Sul. All rights reserved.This study aimed to identify, map, and analyze the research groups (RG) on football in Brazil, through the quantity and quality of the scientific production of research leaders. This is a systematic and descriptive study carried out in the database of the Directory of Research Groups of Brazil of the National Council for Scientific and Technological Development (CNPq). We analyzed the scientific production (2016 and 2022) of the Lattes of the leader’s curriculum. In total, 46 groups were identified, the majority located in the Southeast and South regions of Brazil (n=22/47.8%). The first non-specific RG appeared in 1984 and the first specific RG was registered in 2006. In recent years, these RGs have been responsible for 409 publications about football. It is concluded that there has recently been an increase in RGs, with a trend towards stability in publications, indicating advances in research on football in Brazil.